2002
DOI: 10.1046/j.1440-1681.2002.03712.x
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Administration Of Glucocorticoids Using Surfactant As A Vehicle

Abstract: SUMMARY 1. Glucocorticoids are an effective treatment in the amelioration of chronic lung disease in neonates. However, systemic administration of glucocorticoids to neonates is associated with significant side‐effects that preclude them as an early intervention to prevent onset of the condition. Conversely, local intratracheal administration of glucocorticoids may prevent inflammatory insult to the lungs without the development of systemic side‐effects. We therefore investigated whether local intratracheal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…17,18 However, the results were not constant, and temporal and spatial information could not be attained. Fajardo et al 17 found that both surfactant and saline solution provided an efficient delivery of radiolabeled budesonide to the lungs of rabbits, with the solutions being equally effective.…”
Section: Discussionmentioning
confidence: 97%
“…17,18 However, the results were not constant, and temporal and spatial information could not be attained. Fajardo et al 17 found that both surfactant and saline solution provided an efficient delivery of radiolabeled budesonide to the lungs of rabbits, with the solutions being equally effective.…”
Section: Discussionmentioning
confidence: 97%
“…Addition of other drugs like surfactant to steroids has been tried and has shown better results 15,18 . The property of surfactant remained the same but still the advantage of steroids could be noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, since administration of aerosolized corticosteroids to the preterm infant has limited effectiveness in preventing BPD and requires a delivery system which cannot guarantee selective delivery of inhaled steroids to the alveoli [38], their direct intratracheal administration using surfactant as a vehicle may be a suitable way to deliver topical steroids and thus avoid their side effects on cardiovascular function, glycemia, the immune system, and neurodevelopment, while maintaining their favorable effect on lung tissues. On the other hand, Nimmo et al [39] have previously demonstrated that natural surfactant is an effective vehicle for pulmonary delivery of corticosteroids. The possible absorption of beclomethasone administered through the intratracheal route has not been investigated so far, but data from studies on its intranasal use suggest that the propionate ester of this agent (which was used in our study) is highly lipophilic, and this favors its mucosal absorption and uptake across phospholipid cell membranes with negligible systemic absorption [40].…”
Section: Discussionmentioning
confidence: 99%